Preparation of the market study for the creation of the observatory of foreign trade and foreign investment - Morocho Terán, Johanna Elizabeth (SATHIRI, 2020)
The Foreign Trade career in its quest to provide quality education and continuous improvement seeks to present research projects that bring students closer to the reality of the area, in which they enhance their professional strengths, personal and humanistic skills, in This virtue is proposed to create an Observatory of foreign trade and foreign investment that is linked to the theoretical and practical knowledge that students of the career receive, for this it is proposed to develop a market study to analyze the feasibility of the foreign trade and investment observatory foreigner from the University of Otavalo. The study is descriptive and with a qualitative approach, the sample is of 704 microentrepreneurs, and 9 interviewed among presidents of associations and chambers of commerce of the cantons Cayambe, Ibarra, Antonio Ante, Otavalo, Cotacachi, Tulcán, from the results obtained 94% acceptance is found for the creation of the Observatory, and the main products that microentrepreneurs would need from the Observatory are obtained, among them are knowledge of export, import, international relations, and foreign investment.